Management of coaching-based academic supervision by principals to improve teacher performance in cianjur regency - Gandi Wibowo; Helmawati (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the management of coaching-based academic supervision in improving teacher performance at SDN Wanasari, Agrabinta District, Cianjur Regency. Coaching-based academic supervision integrates John Whitmore’s coaching principles with George R. Terry’s management functions, including planning, organizing, implementing, and evaluating, to encourage teachers to become reflective, innovative, and self-directed in their professional development. This study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and document analysis over three months, involving the school principal and two classroom teachers as main informants. Data analysis followed Miles, Huberman, and Saldaña’s (2014) interactive model, supported by triangulation and member checking to ensure validity. Findings show that supervision planning was participatory, identifying teacher needs and arranging flexible schedules. Organizing emphasized collaborative coordination and communication, fostering a culture of shared leadership. Implementation followed three stages (pre-observation, observation, post-observation) using a dialogical approach guided by the GROW model, enhancing teachers’ reflection, pedagogical competence, and confidence. Evaluation focused on joint reflection and follow-up development, rather than administrative assessment. Main challenges included time constraints, teacher resistance, and limited coaching competence of the principal, addressed through flexible scheduling, personal mentoring, and peer collaboration. This study extends existing literature by demonstrating that the effectiveness of coaching-based supervision depends not only on coaching techniques but also on systematic management by school leaders. Practically, the study recommends participatory planning, transparent organizing, reflective coaching dialogues, and developmental evaluation, enabling academic supervision to function as transformative leadership that enhances teacher professionalism and overall learning quality.